The impact of non-adherence to medication in patients with schizophrenia on health, social care and societal costs. Analysis of the QUATRO study. (10th April 2013) - King, D.; Knapp, M.; Patel, A.; Amaddeo, F.; Tansella, M.; Schene, A.; Koeter, M.; Angermeyer, M.; Becker, T.
Abstract : Aims: For people with schizophrenia, non-adherence to antipsychotic medications may result in high use of health and other services. The objective of our research was to examine the economic consequences of non-adherence in patients with schizophrenia taking antipsychotic medication. Methods: Data were taken from QUATRO, a randomized controlled trial that drew a sample of adults with schizophrenia receiving psychiatric services in four European cities: Amsterdam, Leipzig, London and Verona. Trial inclusion criteria were a clinical diagnosis of schizophrenia, requiring on-going antipsychotic medication for at least 1-year following baseline assessment, and exhibiting evidence of clinical instability in the year prior to baseline. The patient-completed Medication Adherence Questionnaire (MAQ) was used to calculate the 5-point Morisky index of adherence. Generalized linear models (GLM) were developed to determine the effect of adherence on (i) health and social care and (ii) societal costs before and after treatment, taking into account other potential cost-influencing factors. Results: The effect of non-adherence on costs was mixed. For different groups of services, and according to treatment group assignment, non-adherence was both negatively and positively associated with costs. Conclusions: The impact of non-adherence on costs varies across the types of services used by individuals with schizophrenia.